Comparison of Diagnostic Accuracy of Appendicitis Inflammatory Response Score and Alvarado Score in Diagnosis of Acute Appendicitis Taking Histopathology as Gold Standard - Tahira Tariq, Hina Rehman Siddiqui, Imran Ahmed Khan, Ayesha Tasneem, Sobia Majeed (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the diagnostic accuracy of appendicitis inflammatory response score and Alvarado score in diagnosis of acute appendicitis taking histopathology as gold standard. Study Design: It is a Cross Sectional Study Study setting and Duration: This study conducted at the Department of General Surgery, Abbasi Shaheed Hospital, Karachi from September 2018 To March 2019. Methods: Alvarado and Appendicitis inflammatory response scores were used to evaluate all patients. For the Alvarado scoring system, a score of 7 or more was considered a high chance of acute appendicitis, while the AIR scoring system required a score of 9 or higher. The findings of the histopathology lab were compared to the test results. Both tests’ results were analysed to determine their sensitivity, specificity, and diagnostic accuracy. Results: For Alvarado score Sensitivity (80.1%), Specificity (92.3%) and accuracy was 81.7%. For AIR score Sensitivity (72.6%), Specificity (94.2%), and accuracy was 75.5%. There were 66.9% male and 33.1% female patients. Right iliac fossa pain was 76.8%, pain migration to right iliac fossa was 63.5%, anorexia was 90.9%. Conclusion: Higher sensitivity and specificity of the Appendicitis inflammatory response score and the Alvarado score were found to outperform the histological findings in appendicitis.